PENGAMPUAN UNTUK PENDERITA PENYAKIT OTAK MULTIPLE SYSTEM ATROPHY (ANALISA PUTUSAN PENGADILAN NEGERI SURAKARTA NOMOR 213/PDT.G/2019/PN.SKT.) - Ghina Daifinah; Arsin Lukman (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
In course to carry out a legal act, a person must meet the qualification requirements one of which is not under custody. Custody is a form of representation that is carried out by a person to legal subjects who are not legally capable, in this case an incompetent adult. Brain disease is one of the requirements for people who are capable of age but under custody, where the custodian is a person can be trusted to carry out their legal actions and the person under his or her custody. Request for custody must be submitted to the District Court.